Unconstrained metacarpophalangeal joint arthroplasties: a systematic review. Issue 1 (January 2017) - Aujla, R. S.; Sheikh, N.; Divall, P.; Bhowal, B.; Dias, J. J.
Abstract : Aims: We performed a systematic review of the current literature regarding the outcomes of unconstrained metacarpophalangeal joint (MCPJ) arthroplasty. Materials and Methods: We initially identified 1305 studies, and 406 were found to be duplicates. After exclusion criteria were applied, seven studies were included. Outcomes extracted included pre- and post-operative pain visual analogue scores, range of movement (ROM), strength of pinch and grip, satisfaction and patient reported outcome measures (PROMs). Clinical and radiological complications were recorded. The results are presented in three groups based on the design of the arthroplasty and the aetiology (pyrocarbon-osteoarthritis (pyro-OA), pyrocarbon-inflammatory arthritis (pyro-IA), metal-on-polyethylene (MoP)). Results: Results show that pyrocarbon implants provide an 85% reduction in pain, 144% increase of pinch grip and 13° improvements in ROM for both OA and IA combined. Patients receiving MoP arthroplasties had a reduction in pinch strength. Satisfaction rates were 91% and 92% for pyrocarbon-OA and pyrocarbon-IA groups, respectively. There were nine failures in 87 joints (10.3%) over a mean follow-up of 5.5 years (1.0 to 14.3) for pyro-OA. There were 18 failures in 149 joints (12.1%) over a mean period of 6.6 years (1.0 to 16.0) for pyro-IA. Meta-analysis was not possible due to the heterogeneity of the studies and the limited presentation of data. Conclusion: We would recommend prospective data collection for small joint arthroplasties of the hand consisting of PROMs that would allow clinicians to come to stronger conclusions about the impact on function of replacing the MCPJs. A national joint registry may be the best way to achieve this. Cite this article: Bone Joint J 2017;99-B:100–6.